Sistem Pendukung Keputusan Kelayakan Mendirikan Bangunan Menggunakan MOORA - Rafli Junaidi Kasim; Samsul Bahri; Syukirman Amir; Rudi Prietno; Rahim Jamal; Andi Sunyoto; M. Syukri Mustafa (Ikatan Ahli Informatika Indonesia, 2021)
The selection of the feasibility of building a building permit is one of the tasks of the Ternate City Investment and One Stop Integrated Service. In building feasibility selection is still done manually by going down a location survey assessing the criteria needed one by one for each proposal without a method that can provide an assessment priority with various criteria including type of building, foundation, building level, building area and walls, there are many criteria for proposals that are submitted to DPMPTSP. Decision Support System (SPK) is needed to facilitate the Investment and One Stop Integrated Service. The system that was built was web-based, in this research it was carried out through literature reviews and direct interviews with DMPTSP employees. The model used is the method of Multy Objective Optimization On The Basis Of Ratio Analysis. The results of the Multy Objective Optimization Method On The Basis Of Ratio Analysis are considered to have a good level of selectivity in determining an alternative, easy to understand and flexible in separating objects to the evaluation process of the decision weight criteria.